Predictors of poor outcome after extra-corporeal membrane oxygenation for refractory cardiac arrest (ECPR): A post hoc analysis of a multicenter database. (January 2022) - Halenarova, Katarina; Belliato, Mirko; Lunz, Dirk; Peluso, Lorenzo; Broman, Lars Mikael; Malfertheiner, Maximilian Valentin; Pappalardo, Federico; Taccone, Fabio Silvio
Abstract: Background: The objective was to assess predictors for unfavorable neurological outcome (UO) in out-of-hospital (OHCA) and in-hospital (IHCA) cardiac arrest patients treated with Extracorporeal cardiopulmonary resuscitation (ECPR). Methods: A post hoc analysis of retrospective data from five European ECPR centers (January 2012–December 2016) was performed. The primary composite endpoint was 3-month UO defined as survival with a cerebral performance category (CPC) of 3–4 or death (CPC 5). Results: A total of 413 patients treated with ECPR were included (median age was 57 [48–65] years, male gender 78%): 61% of patients (n = 250) suffered OHCA. The median time from collapse to ECMO placement was 63 [45–82] minutes. Overall, 81% patients (n = 333) showed unfavorable UO, which was higher in OHCA patients (90% vs 66%), as compared to IHCA. In OHCA, prolonged time from collapse to ECMO initiation (OR 1.02, p < 0.01) and higher ECMO blood flow (OR 1.99, p = 0.01) were associated with UO while initial shockable rhythm (OR 0.04, p < 0.01), previous heart disease (OR 0.20, p < 0.01) and pre-hospital hypothermia (OR 0.08, p < 0.01) had a protective role. In IHCA, prolonged time from arrest to ECMO implantation (OR 1.02, p = 0.03), high lactate level on admission (OR 1.15, p < 0.01) and higher body weight (OR 1.03, p < 0.01) were independently associated with UO. Conclusions: IHCA and OHCA patients receiving ECPR have different predictors of UO at presentation, suggesting that selection criteria for ECPR should be decided according to the location of CA. After ECMO initiation, ECMO blood flow management and mean arterial pressure targets might also impact neurological recovery.